Inhibition of soleus Hoffmann reflex by ankle–foot orthosis application in healthy volunteers. (December 2015) - Larsen, Lars E; Jakobsen, Lydia A; Jensen, Anne; Lambden, Benjamin M; Sørensen, Morten R; Ellrich, Jens
Background: An ankle–foot orthosis is suggested to actively assist dorsiflexion of the foot by induction of a positive proprioceptive impact to ankle dorsiflexor muscles. However, an objective proof is missing. Objectives: To assess the proprioceptive impact of an ankle–foot orthosis application by Hoffmann reflex recordings of the soleus muscle under static conditions. It was hypothesized that the use of an ankle–foot orthosis facilitated dorsiflexor motor function and thus a decreased the soleus Hoffmann reflex. Study design: Experimental study in healthy volunteers, pre–post test design. Methods: In all, 20 healthy volunteers were enrolled in order to assess the proprioceptive impact of orthosis application. The Hoffmann reflex was recorded before, during, and after orthosis application. Results: Under orthosis application, the Hoffmann reflex significantly decreased as compared to before ( p < 0.05) and after application ( p < 0.05). Conclusions: Findings indicate an inhibition of plantarflexors probably induced by facilitation of ankle dorsiflexors under static conditions. At first glance, it seems that foot orthoses primarily have a stabilizing effect on ankle joints in terms of simple mechanical bandages. However, the present results suggest an additional active impact on proprioceptive control. Clinical relevance: The putative neuromodulatory effect on motor control may support the application of such ankle–foot orthoses in, for example, drop foot. Furthermore, the objective assessment of a neurophysiological mode of action of orthoses by Hoffmann reflex recordings might be an appropriate primary outcome parameter in clinical trials.